Tradisi Lisan Budaya JawaTedhak Siten di Kebondalem Kidul Prambanan Menggunakan Perspektif Semiotika Pierce - Karimah, Aisyah Akhlaqul; Siti Kussuji Indrastuti, Novi; Ra’is Zhaliifunnas, Muhammad (Humanis, 2025)
This research analyzes the tedhak siten tradition in Kebondalem Kidul, Prambanan, using Pierce's semiotic perspective. The study is qualitative, employing observation, interviews, and literature review, with a focus on icons, indexes, and symbols within the tradition. This approach explores how knowledge and cultural values are preserved and conveyed through ritual narratives, prayers, and ceremonial practices of tedhak siten. Data triangulation is used to ensure credible data. The findings reveal that the Tedhak Siten tradition is rich in symbolic meanings, reflecting the cultural identity and values of the local community. The ceremonial processions include stepping on seven-colored prayer beads, climbing up and down wulung sugarcane stairs, and scattering undhik-undhik. Prayers before the procession seek protection and blessings from Allah SWT for the child. This research enhances understanding and appreciation of local cultural diversity and contributes to the study of oral literature and cultural anthropology.